Facilitators to vaccination among hesitant adopters. Issue 12 (2nd December 2021) - Hallgren, Emily; Moore, Ramey; Purvis, Rachel S.; Hall, Spencer; Willis, Don E.; Reece, Sharon; CarlLee, Sheena; Gurel-Headley, Morgan; McElfish, Pearl A.
ABSTRACT: To end the COVID-19 pandemic, it is essential to increase vaccine coverage in the United States (U.S.). In this study, we examine the facilitators that helped hesitant adopters – those who are both vaccinated and report some degree of hesitancy – overcome barriers to vaccination. Drawing on a sample of 867 hesitant adopters in Arkansas, we find social networks, individual actions, health care organizations and professionals, employers, religious communities and leaders, and the media all play a role in helping the vaccine hesitant overcome barriers to vaccination. Our findings demonstrate vaccine hesitancy and uptake occur simultaneously, and overcoming hesitancy in the U.S. population requires multifaceted strategies from multiple entities. We provide recommendations for overcoming barriers, including hesitancy, based on our findings.